Pelatihan Perhitungan Harga Pokok Produksi Mie Sawi Hijau di Desa Pejarakan Karya Kecamatan Ampenan - zeamita; Husni, Syarif; Yusuf, M.; Nursan, Muhammad; Apriana, Anna (Lembaga Dongan Dosen, 2024)
The calculation of cost of goods produced is one of the important activities carried out by MSMEs in calculating the costs incurred to produce a product. Green mustard noodles are one of the green mustard preparations that have added value and provide higher profits for green mustard farmers in Pejarakan Karya Village, Ampenan District. Calculation of the cost of production is needed by farmers to help farmers determine the right and competitive selling price. Currently, farmers do not have the knowledge and skills to calculate the cost of production, making it difficult for farmers to determine the selling price of mustard green noodles. therefore, training on the calculation of the cost of production is needed. the method of service activities is carried out using participatory methods. The service activity of calculating the cost of goods produced (HPP) has generally been carried out well. This can be seen from the increase in farmers' knowledge and skills in calculating the cost of production.